2018
DOI: 10.1155/2018/1486261
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of 0.25% Levobupivacaine, 0.25% Ropivacaine, and 0.25% Bupivacaine in Paediatric Single Shot Caudal Block

Abstract: Aim There are limited data comparing levobupivacaine, ropivacaine, and bupivacaine in paediatric patients. So, this study was performed to evaluate the caudal effectiveness of all the three drugs in paediatric patients undergoing infraumbilical surgeries and associated complications with these drugs. Material and Methods 90 patients of ASA grade I and II posted for elective infraumbilical surgeries were randomly divided into three groups of 30 each. A standardized anaesthetic protocol was used. Patients receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The expected adverse reactions were inadequate analgesia, local reaction to the anaesthetic, and delayed urine derivation in the post-operative period (albeit very rare in children). However, adverse reactions were not reported, which is in line with previous studies (7,9,20,21).…”
Section: Interpretation Of the Study Resultssupporting
confidence: 91%
“…The expected adverse reactions were inadequate analgesia, local reaction to the anaesthetic, and delayed urine derivation in the post-operative period (albeit very rare in children). However, adverse reactions were not reported, which is in line with previous studies (7,9,20,21).…”
Section: Interpretation Of the Study Resultssupporting
confidence: 91%
“…The studies done by Chipde et al 6 , Ray et al 7 and Tambey et al 8 also showed that duration of analgesia provided by caudal Ropivacaine and Bupivacaine were similar. However studies by Locatell et al 9 , Soujanya et al 10 , and Sharma et al 11 showed significant longer duration of analgesia in Bupivacaine group.…”
Section: Discussionmentioning
confidence: 88%
“…In another study, comparing analgesia after brachial plexus block using levobupivacaine and ropivacaine, there was also no difference between the groups with respect to postoperative analgesia 17 . Another study found no difference in pain control using 0.25% levobupivacaine, 0.25% ropivacaine and 0.25% bupivacaine 18 .…”
Section: Discussionmentioning
confidence: 96%